2018
DOI: 10.1111/bcp.13698
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single and multiple doses of elobixibat, an ileal bile acid transporter inhibitor, on chronic constipation: A randomized controlled trial

Abstract: AimsElobixibat is a minimally absorbed ileal bile acid transporter inhibitor. This study aimed to investigate the safety, tolerability, efficacy, pharmacokinetics and pharmacodynamics of elobixibat in Japanese patients with chronic constipation.MethodsThis study consisted of single‐dose and multiple‐dose tests with a dose‐escalating design. Sixty patients including females and males were randomized into five dose levels of elobixibat (2.5, 5, 10, 15 or 20 mg, n = 10 per level) and corresponding placebo (n = 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
2
29
1
Order By: Relevance
“…Elobixibat was reported to lower serum LDL cholesterol by approximately 10% [29]. However, in this study, the LDL and HDL levels did not change significantly after elobixibat administration for 4 weeks.…”
Section: Discussioncontrasting
confidence: 76%
“…Elobixibat was reported to lower serum LDL cholesterol by approximately 10% [29]. However, in this study, the LDL and HDL levels did not change significantly after elobixibat administration for 4 weeks.…”
Section: Discussioncontrasting
confidence: 76%
“…Elobixibat is a minimally absorbed ileal bile-acid-transporter inhibitor and is used clinically to treat constipation by augmenting the level of BA that flows to the colon. Increased dosage causes an increased frequency of diarrhea and corresponding abdominal symptoms [38], as BA can affect stool consistency or cause liquefying of the stool.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacodynamic assessment of EXB in a Japanese phase I study showed decreased serum low-density lipoprotein cholesterol (LDL-C) levels in groups that received repeated doses of ≥5 mg EXB. 8 In addition, a study on NAFLD mouse model reported that treatment with another IBAT inhibitor (IBATi) promoted BA biosynthesis from cholesterol, which accumulated in the liver of mice that received a high-fat diet. 9 Furthermore, converting the BA pool in the liver into hydrophobic BAs decreases hepatic cholesterol accumulation via farnesoid X receptor (FXR) activation, thereby improves the NAFLD status.…”
Section: Introductionmentioning
confidence: 99%